Do relationship investment plans increase couples’ commitment to therapy? - Eisert, Brady Christopher (Kansas State University, 2024)
Dropout in couple therapy is higher than individual or family therapies. Up to 60% of couples do not complete their treatment plans, which is concerning given the investment in time, money, and energy that goes into therapy. The Relationship Investment Plan (RIP) was created at a Midwestern relationship therapy clinic to harness clients’ self-determined motivation to commit to therapy by providing a discount for services within a given subscription period. A Bayesian generalized linear mixed model of 532 cases was used to assess the efficacy of the RIP with both fixed and therapist-varying effects. The final model revealed that RIP enrollment was associated with attending over twice the number of post-intake sessions, fixed across therapists. Therapist experience had therapist-varying (random) effects on retention, and the average number of sessions attended by couples varied by therapist. The relationship length of the couple as well as using a mixed format of therapy (both in-person and telehealth) were also associated with more sessions. Results are discussed in light of the sample and method. Clinical implications regarding the implementation of the RIP are provided.
Keywords: Bayesian generalized linear mixed model; Couple therapy; Dropout; Relationship Investment Plan